Novel Platinum Derivatives Loaded Targeted Nanoemulsions for Improved Potency [30Q]. (May 2016) - Patel, Niravkumar; Piroyan, Aleksandr; Davis, Barbara; Coleman, Timothy
Abstract : INTRODUCTION: Platinum based chemotherapy, introduced four decades ago, is widely used against many types of cancers. It faces challenges such as dose limiting toxicities, cumulative side effects and multidrug resistance. Nanoemulsions have shown tremendous potential in overcoming these challenges as it can be designed to improve circulation time, to improve tumor tissue uptake, and to improve cellular uptake by surface modification. Three novel difatty acid platinums, dimyrisplatin, diplamiplatin, and distearyplatin, those can be sequestered in the oil core of a nanoemulsion, were synthesized, characterized by NMR and elemental analysis as well as evaluated for their potency. METHODS: Nanoemulsions were synthesized using high shear microfluidization process and characterized for size, zeta and loading efficiency. In vitro cytotoxicities were measured by MTT assay. Pharmacokinetic profiles were studied in Balb/c mice. RESULTS: NEs system loaded with platinum variants are highly stable and had size distribution in the range of 100–150 nm. Cytotoxicity data indicates the longer the fatty acid chains, the less potent the nanoemulsions. However, when C6-Ceramide, the apoptosis enhancer, and folate targeting is used to functionalize, the nanoemulsions in vitro potency significantly increases. Upon examining pK data, circulation time for all three variants appeared to remain identical, indication of unaltered residence time of lipidated platinums in nanoemulsions. CONCLUSION: Platinum dimyrisplatin loaded nanoemulsions were most potent in vitro and demonstrated identical pharmacokinetic profile as other variants. These data warrants further clinical development of dimyrisplatin loaded nanoemulsions against MDR tumors.